Humanitas consolatur - Lucija Krešić Nacevski (ed.); Sarakinski, Vojislav (ed.) (Faculty of Philosophy in Skopje, 2025)
If the term humanitas had consistently meant “consolation” throughout the entirety of Roman and later Latin literature, medieval and early modern alike, there would never have been any need for a volume such as this. It is precisely the richness and variability of its meaning, shifting from period to period, genre to genre, author to author, and so on, that has made the term so conceptually challenging. This very complexity has drawn the full attention of the editors of the present volume, who have brought together this collection of essays by our esteemed colleagues, all centered on the exploration of a single, yet remarkably multifaceted concept: humanitas [...] That the question of humanitas remains urgently relevant today is evident in everyday life – in the people we meet and speak with, the films we watch, the books we read, the institutions we attend. [...] We are all too familiar with the attitude found in every period of human history – that the present age is the worst yet, and that anything of true value lies far behind us. Convinced that this is not the case, we present this volume ad legendum vobis studentibusque, in the hope of recognizing and reaffirming eternal values.
Keywords: Education, Ancient Greek ethics, Humanitas, Paideia, Ancient Roman Ethics